The prospective, non-interventional, pharmaco-vigilant study of antibiotic treatment of pediatric patients in pediatric intensive care unit and in-patient wards suffering from sepsis in a tertiary care hospital - Bhattacharyya, Subhradipta; Mohanty, Manjushree (International Journal of Basic & Clinical Pharmacology, 2018)
Background: Sepsis with septic shock has remained a dreadful disease inspite of early intervention mostly due to lack of sensitivity to first line antibiotics. This observational study was conducted to evaluate the utilization of antimicrobials and sensitivity-resistance pattern in paediatric patients suffering from sepsis due to various causes. Methods: A prospective, non-interventional, pharmaco-vigilant study. 38 patients suffering from sepsis admitted in paediatric ward and PICU from September 2012 to February 2014 were evaluated. The research protocol was approved by Institutional Ethical Committee, KIMS. Data were collected from case sheets of patients from the ward as well as Medical Record and Data section. Average of Data on a continuous scale was expressed as a mean along with standard deviation, Categorical data was expressed as percentage. Comparative statistical analysis was done by using student’s t-test in respect of data measured on a continuous scale. All differences with P value below 0.05 were labelled as statistically significant. Results: Total 38 patients were admitted with provisional diagnosis of sepsis. 52.5% patients were suffering from ≥2 diseases while pneumonia (64%) and meningitis (22%) were observed to cause sepsis. 10(27%) patients presented with septic shock while 39.3% patients having single organ failure and 10.4% patients having multiple organ failure. inj Dopamine (33%) and inj Dobutamine 11% were used and ventilator was used in 1 patient. Most of the patients received multiple antibiotics in I.V. route, 30 (79%) patients received ≥3 antibiotics. Linezolid+ piperacillin+ tazo + aminoglycoside + 4th drug combination was observed to be used in 34% patients while Linezolid+ 3rd gen. cephalosporin+ aminoglycoside+ 4th drug combination was used in 21% patients. Cephalosporin was most frequently withdrawn antibiotic (47 % of use). High resistance was observed for both gram +ve and gram -ve bacteria against cephalosporin. Conclusions: Anti-MRSA agents (Linezolid) and anti-MDR GNB agent (Meropenem) significantly used to control the severe sepsis in conjunction to Piperacilin/ ceftriaxone + amikacin.